Effect of accelerated weathering test on selected properties of bamboo, Scots pine and Oriental beech wood treated with waterborne preservatives : Utjecaj ubrzanog izlaganja vremenskim utjecajima na svojstva bambusa, drva bora i drva bukve obrađenih zaštitnim sredstvima na bazi vode - Topaloglu, Elif (Array, 2019)
This paper investigates the changes in density, compression strength parallel to grain, static modulus of rupture and modulus of elasticity of untreated (control) and waterborne-treated bamboo (Phyllostachys bambusoides), Scots pine (Pinus sylvestris) and Oriental beech (Fagus orientalis) specimens subjected to accelerated weathering using an accelerated weathering chamber for 672 hours. Wolmanit-CB (CCB), tanalith-E (Tan-E), amine copper quat-1900 (ACQ) and boric acid-borax (BB) were used as waterborne preservatives. The retention value of bamboo specimens was lower than that of wood specimens due to the difference in anatomical structure of bamboo. The value of density, compression strength parallel to grain, static modulus of rupture and modulus of elasticity of treated bamboo and wood were generally higher than those of untreated specimens after accelerated weathering. ACQ treatment generally provided the best protection against weathering in all mechanical tests for both bamboo and wood specimens, while CCB treatment provided an effective protection against weathering in compression strength for Oriental beech. BB treatment provided the least protection against weathering for bamboo and wood specimens compared to other waterborne preservatives.